The role of male caretakers and pre-school teachers for father involvement in ECEC - Tim Rohrmann (Global Education Review, 2019)
‘Children need men!’ This rallying cry is a common argument for father involvement in the family as well as in the context of strategies for more men in ECEC. In what way are these two issues linked? Based on international research on the issue, this paper asks what role male EC workers can have for the involvement of fathers in the work of ECEC institutions / pre-schools. A critical gender perspective is crucial for the understanding of these links.